POTENTIAL ANALYSIS OF MOSQUE WUDHU WASTE AS A PICOHYDRO POWER PLANT - Cut Taffazani Fithrian Nazla; Syafrina Sari Lubis (Chimica Didactica Acta, 2021)
Ablution is a ritual activity that is quite important in the implementation of prayer. The amount of waste water produced by Ablution activities is large and the reserves are abundant. It is estimated that in one month a mosque with 4325 visitors per week who performs ablution produces 86.5 m3/person/month of ablution waste. This potential waste can be used for various purposes such as watering plants, or aquaculture, and as a pico hydro power plant. The Pico hydro power plant is a term used for hydroelectric power generation capacities below 5 KVA or even smaller, ranging from 200-300 VA. Pico hydro can be generated from a turbine, which is rotated by the natural water flow at a minimum of one meter inclination, the power generated is not too large and is suitable for simple electrical equipment. Ablution waste has the potential to be developed as a pico hydro power plant.